PENGARUH DEBT TO EQUITY RATIO, COLLATERALIZABLE ASSET, SALES GROWTH, FREE CASH FLOW DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Muslih, Muhamad; Rahmi Husin, Elsa (EDUTECH CONSULTANT, 2019)
This study aims to determine the effect of debt to equity ratio (DER), collateralizable assets (COLLAS), sales growth (SG), free cash flow (FCF) and company size (SIZE) on dividend policy (DPR) in companies in the Industrial sector of Consumer Goods listed on the Indonesia Stock Exchange in 2013-2017. The data used in this study was obtained from financial report data taken from the official website of the Indonesia Stock Exchange. The population in this study is the consumption goods industry sector companies listed on the Indonesia Stock Exchange in 2013-2017. The sampling technique used was perposive sampling and obtained 13 companies with a research period of 5 years, so that 65 sample data were obtained. The method of data analysis in this study is panel data regression analysis using software eviews 9.0. The results of the study show that simultaneously the debt to equity ratio (DER), collateralizable assets (COLLAS), sales growth (SG), free cash flow (FCF) and company size (SIZE) has a significant effect on dividend policy (DPR). While partially the debt to equity ratio (DER) and collateralizable assets (COLLAS) have a significant effect on the negative direction of dividend policy (DPR). Company size (SIZE) has a significant effect on the positive direction of dividend policy (DPR). Sales growth (SG) and free cash flow (FCF) variables have no significant effect on dividend policy with a positive direction.